2014
DOI: 10.1128/aem.00957-14
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Decomposition Is Accelerated by Soil Microbes

Abstract: f Carrion decomposition is an ecologically important natural phenomenon influenced by a complex set of factors, including temperature, moisture, and the activity of microorganisms, invertebrates, and scavengers. The role of soil microbes as decomposers in this process is essential but not well understood and represents a knowledge gap in carrion ecology. To better define the role and sources of microbes in carrion decomposition, lab-reared mice were decomposed on either (i) soil with an intact microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 31 publications
3
59
0
1
Order By: Relevance
“…Studies of cadaver decomposition and its interactions with, and effects on, soil ecology have highlighted the potential of forensic ecogenomics as a powerful tool to estimate PMI and identify clandestine graves through changes in microbial communities [14][15][16][20][21][22][23]. Although this tool has potential advantages compared with conventional methods for estimating PMI, most studies have, however, only considered a single carbon source (the cadaver) while dual sources can provide useful information for forensic practitioners to identify and differentiate gravesites in difficult cases such as transit or clandestine scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of cadaver decomposition and its interactions with, and effects on, soil ecology have highlighted the potential of forensic ecogenomics as a powerful tool to estimate PMI and identify clandestine graves through changes in microbial communities [14][15][16][20][21][22][23]. Although this tool has potential advantages compared with conventional methods for estimating PMI, most studies have, however, only considered a single carbon source (the cadaver) while dual sources can provide useful information for forensic practitioners to identify and differentiate gravesites in difficult cases such as transit or clandestine scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some sub-surface studies by Bergmann et al [19] and Olakanye et al [20] recorded spatial and temporal changes in soil bacterial diversity relative to burial depth and decomposition time, respectively. Also, aboveground studies by Lauber et al [21] that investigated the roles of microorganisms in cadaver ecogenomics recorded changes in 16S rRNA bacterial, 16S rRNA archaeal, and 18S rRNA fungal communities in sterile and non-sterile soils with differences between skin-associated and grave soil during the active and advanced decay stages. Thus, several researchers have illustrated and suggested that changes in epinecrotic and burial soil microbial diversity can be a potential "post-mortem microbial clock" tool for PMI estimation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…temperature, moisture, vegetation, and pH [8,7,[9][10][11]. Microbial gravesoil activity is primarily driven by bacteria during the early stages of decomposition [3,12], followed by increased activity of eukaryotes, such as nematodes [3] and fungi [13,14], during later stages of decomposition. Yet, one variable has received little experimental attention: the mass of the corpse.…”
mentioning
confidence: 99%
“…However, the scarce information on the microbial decomposition of human cadavers and animal carcasses indicates that the so-called decomposer (or saprophage, saprophyte, saprobe) microorganisms of the outside environment (soil, mud, or water) play a subordinate role in this process (though it may still be relevant in small-bodied animals, see Lauber et al, 2014). The main direction of bacterial decomposition is from the inside out: in nematodes (Cabreiro and Gems, 2013), arthropods (Butler et al, 2015), as well as in humans (Hyde et al, 2013;Palmiere et al, 2015;Can et al, 2014) it is members of the former healthy microbiome that constitute the dominant actors of microbial decomposition of carcasses and cadavers.…”
Section: The Role Of Sepsis-inducers In Cadaver Decompositionmentioning
confidence: 99%